The eight hundred [videorecording (DVD)] - Guan, Hu; Guan, Hu; Huang, Zhizhong, 1978-; Zhang, Junyi (Actor); Ou, Oho, 1992- (Shout! Factory, 2021)
Based on a true story, outnumbered and under-equipped Chinese soldiers defend the Sihang Warehouse from the Imperial Japanese Army during the battle of Shanghai.